Scaling Gem Parboiling And Rice By-Products: Insights And Lessons Learned From 2022 To 2025 - Dossou Yovo, Elliott Ronald; Diabate, Fatoumata; Suh, Neville Ndohnwi (2025)
Parboiling and the valorisation of rice by-products play an increasingly critical role in strengthening climate resilience, food security, and women’s economic empowerment within Mali’s rice-based systems. As climate change intensifies production risks through unpredictable rainfall, floods, droughts, and declining soil fertility, post-harvest innovations have emerged as key adaptation strategies that ensure both value addition and reduced losses. From 2022 to 2025, the AICCRA Mali project scaled climate-smart innovations such as the GEM (Grain quality–Energy–Maintenance) parboiling technology and by-product processing to enhance grain quality, nutritional value, income generation, and gender equity across rice value chains. Over 250 women, particularly from cooperatives, are using the GEM paboiler technology, supporting household income and nutrition while reducing greenhouse gas emissions in rice-based systems in Mali. To continue strengthening the capacity of rice value chain actors and scaling the GEM parboiling technology and volatilization of rice byproducts, a one-day capacity-building workshop was held in Bamako.